The effectiveness of marketing strategy in Bank Rakyat at Jalan Hang Tuah, Melaka / Lilisari Abdul Rahim - Abdul Rahim, Lilisari (Faculty of Business and Management, 2008)
This study is based on the research of "The Effectiveness of Marketing Strategy in Bank Rakyat at Jalan Hang Tuah, Melaka". The aim of this study is to identify the most effective marketing strategy that has been implemented in Bank Rakyat at Jalan Hang Tuah Melaka (BR JHTM). The marketing strategy that has been stated are the product, price, place, people, promotion and social responsibilities. Meanwhile, this research also want to explore what is the best suggestion given by the customer in order to improve Bank Rakyat at Jalan Hang Tuah Melaka performance. Not only that, the researcher also wants to identify the relationship between those marketing strategy towards the performance of Bank Rakyat at Jalan Hang Tuah Melaka. 50 questionnaire has been distributed to the respondents in order to fill out the entire question. The result will be gain after the analysis and interpretation of data. The respondents mostly are the customers who have used the products and services from Bank Rakyat at Jalan Hang Tuah Melaka. From the analysis, researcher found out that the most effective marketing strategy is people. Besides, by using the cross tabulation, researcher found out that there is no relationship between certain variables of marketing strategy and BR JHTM performance.